ENVIRONMENTAL COMMUNICATION STRATEGY IN MINIMIZING FOOD WASTE AT KFC MEDAN - Bintang Zalukhu; Solihah Titin Sumanti (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
The goal of this study is to outline how environmental communication methods helped KFC Medan reduce food waste. This study adopts a descriptive methodology and qualitative research techniques. On the basis of primary and secondary data, data sources are chosen. The key informant chosen for this study was HR KFC in the regions of North Sumatera and Aceh. According to the study's findings, 1) There are supporting and inhibiting factors in the environmental communication process at KFC Medan, but all of them can be properly overcome based on specific mechanisms from the leadership to KFC, and 2) There are communicators, environmental communication messages, environmental communication media, and communicants who play a role in the process. The environmental communication strategy that has been carried out by KFC Medan includes 4 components that play a role, namely communicators, environmental communication messages, environmental communication media, and communicants. In addition, there are several factors in it, namely supporting factors and inhibiting factors during the environmental communication process at KFC Medan. However, everything can be overcome properly based on certain mechanisms from the leadership to the employees at KFC Medan. However, KFC Medan does not mind if the food that has been ordered by cosumers or customers is not finished or still left. Because according to KFC Medan, it is the consumer's right to finish food or not to finish the food that has been ordered by the consumers. Advice for researchers to KFC Medan to also provide education related to food waste to consumers, so that environmental communication related to food waste is not limited to leaders and employees and every consumer can be involved in it. The researcher's suggestion for other researchers who will continue similar research is expected to contribute to conducting research in restaurants and make restaurants or food companies that initially only carry out environmental communication strategies related to food waste limited to leaders and employees, can be applied by restaurants or food companies to consumers as well.